2021
DOI: 10.3390/nu13072178
|View full text |Cite
|
Sign up to set email alerts
|

The Olive Leaves Extract Has Anti-Tumor Effects against Neuroblastoma through Inhibition of Cell Proliferation and Induction of Apoptosis

Abstract: Neuroblastoma (NB) is the most common extra-cranial solid tumor of pediatric age. The prognosis for high-risk NB patients remains poor, and new treatment strategies are desirable. The olive leaf extract (OLE) is constituted by phenolic compounds, whose health beneficial effects were reported. Here, the anti-tumor effects of OLE were investigated in vitro on a panel of NB cell lines in terms of (i) reduction of cell viability; (ii) inhibition of cell proliferation through cell cycle arrest; (iii) induction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
(61 reference statements)
0
15
0
Order By: Relevance
“…Caspase-9 is a protease that is involved in the apoptotic process, and has been related to mitochondrial damage. An earlier study suggested that aqueous OLE exhibited anti-apoptosis markers by reducing the levels of caspases 3 and 9 due to the presence of oleuropein and hydroxytyrosol (Morandi et al, 2021). Yaguchi et al (2010) reported the inhibitory effect of linoleic acid on caspases 3 and 9.…”
Section: Results Results Resultsmentioning
confidence: 99%
“…Caspase-9 is a protease that is involved in the apoptotic process, and has been related to mitochondrial damage. An earlier study suggested that aqueous OLE exhibited anti-apoptosis markers by reducing the levels of caspases 3 and 9 due to the presence of oleuropein and hydroxytyrosol (Morandi et al, 2021). Yaguchi et al (2010) reported the inhibitory effect of linoleic acid on caspases 3 and 9.…”
Section: Results Results Resultsmentioning
confidence: 99%
“…Researchers have shown that the anti-tumor effects of many drugs can be achieved by inducing tumor cell apoptosis [ [16] , [17] , [18] ]. To prove this, 143B cells were treated with 20 and 40 μM concentrations of ISO.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the present results suggest that the interesting activity of PRES was due to all its components and not only to oleuropein-like compounds, the most representative from a quantitative point of view. Data from the literature assessing OE leaf extract anti-tumor activity against different neuroblastoma cell lines, including SH-SY5Y, reported significant loss in cell viability and apoptosis after 72 h treatment with the extract containing 300 µM oleuropein [ 33 ]. Seçme et al directly investigated the anti-tumor efficacy of the single bioactive molecule oleuropein against the SH-SY5Y neuroblastoma cell line, finding an approximate 48 hour-IC 50 of 350 µM [ 34 ].…”
Section: Discussionmentioning
confidence: 99%